Perpetrators' Humanity: War, Violence, and Memory After 1971. (1st October 2016) - Yasmin Saikia
Abstract : How does love for home/nation become the site for intolerance and provoke violence against others? What precipitates the expression of this hate? Is shared humanity possible among erstwhile perpetrators and victims? Through the method of oral history, in this article I probe these questions by investigating the memories of perpetrators of the 1971 war of Bangladesh. A common and shared memory of perpetrators was the humbling experience of fighting a destructive war in which they lost nation as well as their human self. The mournful memories of human loss are explained as the destruction of insāniyat, which opens the space for acknowledging the divergent desires of nationalism that clashed with human ethics. Today, the nations of India, Pakistan, and Bangladesh refuse to acknowledge the disastrous memories of 1971 because it unsettles state written histories. For perpetrators, however, the memories of violence are critical for understanding the meaning of sacrifice on behalf of nation, as well raising for them the question of ethical responsibility to victims. The moral dilemma is an "imprisoned" memory of the loss of insāniyat that cannot be articulated publicly because there is no place for it in Bangladesh and Pakistan. The fragmentary shards of perpetrators' memories express hope for renewing the commitment to insāniyat. This is a challenge and struggle in South Asia that is divided by mythical national histories and the politics of postcolonial nationalism. Without the rethinking of insāniyat at a public level, I'd argue the question of tolerance would remain submerged or become simply a document constructed at supra-national level without anchoring it within culture and society in South Asia.